Peran Pokdarwis Teluk Kiluan dalam Pengembangan Desa Ekowisata - Putri, Ashara; Hidayati, Dewi Ayu (Rumah Jurnal UNEJ, 2024)
The Ecotourism Village of Teluk Kiluan is an ecotourism destination that applies the concept of